2021
DOI: 10.1161/atvbaha.121.316867
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and Molecular Mechanism of AGGF1 Signaling in Endothelial Cell Functions and Angiogenesis

Abstract: Objective: Angiogenic factor AGGF1 (angiogenic factor and G-patch and FHA [Forkhead-associated] domain 1) promotes angiogenesis as potently as VEGFA (vascular endothelial growth factor A) and regulates endothelial cell (EC) proliferation, migration, specification of multipotent hemangioblasts and venous ECs, hematopoiesis, and vascular development and causes vascular disease Klippel-Trenaunay syndrome when mutated. However, the receptor for AGGF1 and the underlying molecular mechanisms remain to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…We recently found that AGGF1 regulated endothelial cell (EC) functions and angiogenesis by interacting with its receptor integrin α5 on endothelial cell surface ( 16 ). As integrin α5 is also expressed in VSMCs, we investigated whether integrin α5 mediated the adhesion of AGGF1 to VSMCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that AGGF1 regulated endothelial cell (EC) functions and angiogenesis by interacting with its receptor integrin α5 on endothelial cell surface ( 16 ). As integrin α5 is also expressed in VSMCs, we investigated whether integrin α5 mediated the adhesion of AGGF1 to VSMCs.…”
Section: Resultsmentioning
confidence: 99%
“…In an accompanying study, we showed that cell adhesion to AGGF1 was not disrupted by neutralizing antibodies against integrins α1, α2, α3, α4, α6, αv, and β3; therefore, these integrins are unlikely to affect the function of AGGF1 in VSMCs. However, we found that integrin α5β1 acted as a receptor for AGGF1 in endothelial cells, activated FAK-Src-AKT signaling, and modulated the signaling and functions of AGGF1 in endothelial cells and therapeutic angiogenesis in a model for peripheral artery disease (PAD) ( 16 ). The question is whether integrin α5β1 also acts as a receptor for AGGF1 in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al revealed that AGGF1 activated the antioxidative processes in EPCs to inhibit reactive oxygen species generation, thus promoting EPCs function in diabetic HLI model mice 115 . Moreover, Wang et al reported integrin α5β1 as a receptor for AGGF1 in ECs could promote ECs adhesion, migration, capillary tube formation, and therapeutic angiogenesis in the HLI mouse model 116 .…”
Section: Trends In Therapeutic Angiogenesis For Padmentioning
confidence: 99%
“…To substantiate the DNA hypermethylation, we used DNA isolated from AVM nidus and control tissue (3rd sample) and performed the promoter DNA methylation analysis for the CpG islands of selected genes. We performed bisulfite conversion and sequencing of the selected gene promoters, which are known to involve in vascular development [16,17,25,31,38]. We selected four genes such as ZNF24 (also known (Kox17), AGGF1 (Angiogenic factor with G patch and FHA domains 1), ANKRD65 (Ankyrin repeat domain 65), and FAAH (Fatty acid amid hydrolase) for further validation of DNA hypermethylation on the promoter of these genes [16,17,25,31,38].…”
Section: Promoter Methylation Analysis Confirms the Aberrant Dna Meth...mentioning
confidence: 99%